Visual prior entry. - Shore, D; Spence, C; Klein, R (2001)
It has long been claimed that attended stimuli are perceived prior to unattended stimuli--doctrine of prior entry. Most, if not all, studies on which such claims have been based, however, are open to a nonattentional interpretation involving response bias, leading some researchers to assert that prior entry may not exist. Given this controversy, we introduce a novel methodology to minimize the effect of response bias by manipulating attention and response demands in orthogonal dimensions. Attention was oriented to the left or right (ie., spatially), but instead of reporting on the basis of location, observers reported the order (first or second) of vertical versus horizontal line segments. Although second-order response biases were demonstrated, effects of attention in accordance with the law of prior entry were clearly obtained following both exogenous and endogenous attentional cuing.